Perioperative platform for muscle-invasive bladder cancer trials: designs and endpoints - Laukhtina, Ekaterina; Moschini, Marco; Teoh, Jeremy Yuen-Chun; Shariat, Shahrokh F (Current opinion in urology, 2025)
PURPOSE OF REVIEW: This review explores the design and endpoints of perioperative platforms in clinical trials for muscle-invasive bladder cancer (MIBC). RECENT FINDINGS: The choice of clinical trial design in perioperative platforms for MIBC must align with specific research objectives to ensure robust and meaningful outcomes. Novel designs in perioperative platforms for MIBC integrate bladder-sparing approaches. Primary endpoints such as pathological complete response and disease-free survival are highlighted for their role in expediting trial results in perioperative setting. Incorporating patient-reported outcomes is important to inform healthcare decision makers about the outcomes most meaningful to patients. Given the growing body of evidence, potential biomarkers, predictive and prognostic tools should be considered and implemented when designing trials in perioperative platforms for MIBC. SUMMARY: Effective perioperative platforms for MIBC trials are critical in enhancing patient outcomes. The careful selection and standardization of study designs and endpoints in the perioperative platform are essential for the successful implementation of new therapies and the advancement of personalized treatment approaches in MIBC.
Keywords: Perioperative Care; stanovení cílového parametru; perioperační péče; invazivní růst nádoru; Clinical Trials as Topic; Research Design; Neoplasm Invasiveness; Humans; cystektomie; výsledek terapie; Cystectomy; nádory močového měchýře; lidé; Urinary Bladder Neoplasms; Endpoint Determination; Treatment Outcome; klinické zkoušky jako téma; výzkumný projekt